Effects of NCAAA Accreditation on Health Sciences Educational Programs: Faculty Experiences at KSAU-HS. - Alhassan, Abdulaziz Ibrahim; Alghamdi, Bayan Mohammad (Journal of Healthcare Leadership, 2026)
Aim: The purpose of this study was to explore the perspectives of faculty at King Saud Bin Abdulaziz University for Health Sciences (KSAU-HS), Saudi Arabia, regarding how National Commission for Academic Accreditation and Assessment (NCAAA) accreditation influences teaching, assessment, and program improvement. Methods: This study utilized a qualitative thematic analysis design in which semi-structured one-on-one in-depth interviews were conducted with educational program directors and faculty members at KSAU-HS across its three campuses in Riyadh, Jeddah, and Al Ahsa. Theoretical saturation was reached after interviewing 15 participants. Results: The results of the study generated three main themes including institutional quality system and continuous improvement under NCAAA, structuring teaching and assessment for validity and fairness, and operational realities and contextual adaptation in implementation. This revealed that faculty generally believed that accreditation brought benefits to the university, yet noted that this process required a great deal of time and work and that some of the accreditation standards were too rigid and inflexible. Conclusion: These findings suggest that universities need to provide support to faculty for accreditation activities and that the NCAAA may need to consider some flexibility in some of its standards.